Growth Story of One Diamond: A Window to the Lithospheric Mantle - Valentin Afanasiev; Sargylana Ugapeva; Yuri Babich; Valeri Sonin; Alla Logvinova; Alexander Yelisseyev; Sergey Goryainov; Alexey Agashev; Oksana Ivanova (Minerals, 2022)
A diamond plate cut out of a transparent, colorless octahedral diamond crystal of gem quality, with a small chromite inclusion in the core, sampled from the XXIII CPSU Congress kimberlite (Yakutia, Mirny kimberlite field, vicinities of Mirny city), has been studied by several combined methods: absorption spectroscopy at different wavelengths (UV-visible, near- and mid-IR); photoluminescence, cathodoluminescence, and Raman spectroscopy (local version) and lattice strain mapping; birefringence in cross-polarized light; and etching. The diamond plate demonstrates a complex growth history consisting of four stages: nucleation and growth to an octahedron → habit change to a cuboid → habit change to octahedron-1 → habit change to octahedron-2. The growth history of the diamond records changes in the crystallization conditions at each stage. The revealed heterogeneity of the crystal structure is associated with the distribution and speciation of nitrogen defects. The results of this study have implications for the information value of different techniques as to the diamond structure defects, as well as for the as yet poorly known evolution of the subcontinental lithospheric mantle in the Siberian craton, recorded in the multistage growth of the diamond crystal. At the time of writing, reconstructing the conditions for each stage is difficult. Meanwhile, finding ways for such reconstruction is indispensable for a better understanding of diamond genesis, and details of the lithosphere history.